DIGITAL TOOLS FOR DEVELOPING ENTREPRENEURIAL AND MANAGERIAL THINKING IN HIGHER EDUCATION - Gayrat Sultanov (Modern American Journals, 2025)
This article explores the integration of digital tools into higher education curricula as a means of fostering entrepreneurial and managerial thinking among students. The study focuses on the relevance and effectiveness of such tools in the context of Uzbekistan’s evolving educational landscape. As educational systems increasingly adopt digitalization, equipping students with future-ready skills becomes essential. The paper highlights the importance of digital simulations, business planning software, and virtual collaborative platforms in enhancing strategic thinking, decision-making, and leadership competencies. The findings suggest that purposeful implementation of these technologies can significantly enrich the learning experience and better prepare students for real-world managerial and entrepreneurial challenges.
Keywords: Digital tools, entrepreneurial thinking, managerial skills, higher education, educational technology, student competencies, virtual learning, innovation in education, Uzbekistan, pedagogical innovation.